The Effect of Profitability, Firm Size, and Leverage on Firm Value (Study on Banking Companies Listed on the Indonesia Stock Exchange in 2018-2023) - Fadhilah, Miftakhul; Widajantie, Tituk Diah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to find out the effect of profitability, firm size, and leverage on firm value. This researh employs quantitative research methodology. The population used in this research is a banking company registered with the IDX for the period 2018-2023. The sampling technique used purposive sampling method. Based on the sample selection criteria, there were 13 companies and 78 samples. The data analysis technique used is multiple linear regression analysis. The SPSS version 25 tool was used to process data in the analysis of this study. The results of this research show that profitability and firm size has a positive effect on firm value in banking companies listed on the IDX in 2018-2023, while leverage has no effect on firm value in banking companies listed on the IDX in 2018-2023. Further research could develop this research using other variables that in theory have an effect on a firm value, such as dividend policies, capital stucture, free cash flow, and others.